PERENCANAAN PERAWATAN LANDAS PACU 11-29 DENGAN MENGGUNAKAN METODE PCI (PAVEMENT CONDITION INDEX) DI BANDAR UDARA HUSEIN SASTRANEGARA - BANDUNG - Sandy Prasetia; SUKAMTO; Luky Surachman (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
Occurring problems in runway 11-29 at Husein Sastranegara Bandung is kind of surface pavement, those problems happen because of continuous usage on it’s surface, pavement durability, and factor of weather, so that flexible pavement currently fragile and easy to get damaged. Evaluations regarding the damage of runway pavement surface using Pavement Condition Index (PCI) and doing action such fixing planning of the evaluation results, so that the sample of the damage overall can be resumed. From the calculation done, it can be conclude that damage found in segment 2 is damage Depression crack 3,37 m3, Block Cracking damage 0,02 m3, segment 19 is damage Ravelling crack 9,13 m3, damage Depression crack 8,39 m3, damage to Rutting crack 29,98 m3, segment 98 is damage Longitudinal/Transverse cracking 1,48 m3, Depression crack damage 5,50m 3, damage Patching crack 0,08 m3, damage Rutting crack 1,78 m3, segment 120 is damage Polished Agregate 0,30 m3, Longitudinal/Transverse cracking 0,70 m3, and segment 170 is Rutting crack damage 44,44 m3, Depression crack damage2,61 m3. So it is necessary to re-coat and do research of pavement layer structure and ground so as to meet CBR/carrying capacity and optimize the implementation of coating